Investigations on the surface, thermo-electrical and mechanical properties of ZBG crystal for optoelectronics applications. (2022) - Mohanraj, K.; Shobana, E.; Chang, J.H.; Ho, Mon-Shu; Babu, B.; Chandrasekar, S.; Gowtham, M.; Senthil Kumar, N.; Jhansi, N.; Balasubramanian, D.
Abstract: The low temperature solution growth method was adopted for growing semi organic single crystal zinc boro glutrate (ZBG). The surface morphology was investigated by SEM analysis. Analysis of microhardness has been done, measurement of the Vickers hardness number Hv. Dielectric studies show a decrease in dielectric loss and dielectric constant with an increase in frequency and a constant value in the higher frequencies, suggesting that the crystal is also of good optical quality in nature.